METHODOLOGY FOR THE USE OF WALKING IN THE SCANDINAVIAN WAY IN THE DEVELOPMENT OF THE ORGANISM OF STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In this article, it was mentioned about the application of Nordic walking for the purpose of productive use of leisure time of Primary School students, as well as its positive impact on the health of students.